2014
DOI: 10.1186/1472-6823-14-14
|View full text |Cite
|
Sign up to set email alerts
|

Association of calcaneal quantitative ultrasound parameters with metabolic syndrome in middle-aged and elderly Chinese: a large population-based cross-sectional study

Abstract: BackgroundThe possible association between metabolic syndrome (MS) and bone mineral density (BMD) has been highlighted recently. However, the exact effects of MS on calcaneal quantitative ultrasound (QUS) parameters remains uncertain. The aim of this study was to assess the impact of MS states, different componets of MS, as well as the number of MS componets on QUS.MethodsA total of 7489 Chinese adults aged 40 years or older in Nanjing were enrolled in this cross-sectional study. MS was defined according to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Cross-sectional study 938 post-menopausal women from Eastern China risk of any fractures compared to non-MetS women. 57 Other studies among the Chinese population also obtained similar findings. 58,59 In contrast to the studies mentioned earlier, the Camargo cohort study found no significant difference in the prevalence of VF and NVF between MetS and non-MetS subjects of either sex.…”
Section: Chen Et Al (2018) 24supporting
confidence: 61%
See 1 more Smart Citation
“…Cross-sectional study 938 post-menopausal women from Eastern China risk of any fractures compared to non-MetS women. 57 Other studies among the Chinese population also obtained similar findings. 58,59 In contrast to the studies mentioned earlier, the Camargo cohort study found no significant difference in the prevalence of VF and NVF between MetS and non-MetS subjects of either sex.…”
Section: Chen Et Al (2018) 24supporting
confidence: 61%
“… 46 A Chinese study (2814 males and 4675 females, ≥40 years) also showed that women with MetS experienced an increased risk of any fractures compared to non-MetS women. 57 Other studies among the Chinese population also obtained similar findings. 58 , 59 …”
Section: Relationship Between Mets and Bone Fracturesupporting
confidence: 61%
“…However, less is known about the effects of MS on bone metabolism. Different reports reveal conflicting results regarding MS or its individual components, with bone mineral density and/or fracture risk [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…MetS is associated with a higher risk of cardiovascular morbidity and mortality and a higher risk of onset of type 2 diabetes. Although the relationship between cardiovascular disease and osteoporosis has been widely studied, the particular association between metabolic syndrome, a strong risk factor for cardiovascular disease, and osteoporotic fractures has not been so extensively addressed and present several studies results were inconsistent [ 5 15 ]. Epidemiological studies on fracture incidence or prevalence are therefore needed in order to show the real pattern of fractures in MetS.…”
Section: Introductionmentioning
confidence: 99%